REVEALING THE IDEAS OF SOCIETY THROUGH CULTURAL MYTHS IN THE NOVEL THE WONDERFUL WIZARD OF OZ BY L. FRANK BAUM - Rachman, Ferdi Sufi; Jepri (Faculty of Letters Universitas Balikpapan, 2025)
This paper studies forms of ideas of society through cultural myths. There are two research questions for this research: What are the forms of ideas of society, and How do the ideas of society reveal through cultural myths in the novel the wonderful wizard of oz? This research aims to uncover the three forms of society as through five cultural myths. This research uses Roland Barthes' semiotic theory and Emile Durkheim's theory of ideas of society, approached through sociological literature. The study employs a qualitative research method to present the findings descriptively. The data is collected from The Wonderful Wizard of Oz, then examined and analyzed the data in the form of excerpts. The result of the research in this study, there are three ideas of society: 1) 19 data of collective notions, 2) 16 data of beliefs, 3) 5 data of conceptual framework. The researcher founds there are four cultural myths that reveal ideas of society: 1) 9 data of moral lessons, 2) 15 data of cultural values, 3) 9 data of societal norms, 4) 7 data of political symptoms. This research found that cultural values reveal collective notions more prominently than the three other cultural myths.